The Importance of Early Arabic Language Learning in the Early Childhood Education Curriculum - Riza Novanto; Dhimas Romadhoni; Widyaningsih Widyaningsih; Chusna Apriyanti (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2026)
This study aims to examine the significance of integrating Arabic language learning into the early childhood education (ECE) curriculum. Arabic, as the language of the Qur'an, plays a crucial role in understanding Islamic teachings and shaping Muslim identity. This research emphasizes the cognitive benefits gained from learning a foreign language at an early age, such as improved memory, problem-solving skills, and cognitive flexibility. Effective teaching methods, including game-based learning, the use of visual media, and communicative approaches, can stimulate children's interest in Arabic. The integration of Islamic values into Arabic language learning is also an essential factor in developing good character and moral values in children. Therefore, this study concludes that introducing Arabic language learning from an early age provides a strong foundation for understanding religion, strengthening Muslim identity, improving communication skills, and preparing children for further education. This qualitative study with a case study design was conducted at PIAUD Dusun Meling, Jetak Village, involving two early childhood teachers and 15 children aged 4–5 years. Data were collected through observation, interviews, and documentation over approximately two months. The findings indicate that the teacher’s role as a play-scenario designer, interaction facilitator, provider of positive feedback, and motivator is crucial. Role-playing methods were found to improve children’s ability to pronounce basic Arabic vocabulary, construct simple sentences, and communicate in real-life situations. The study highlights the importance of optimizing the teacher’s role in role-play methods to enhance Arabic speaking skills among early childhood learners. The implications emphasize the need for social-emotional learning that promotes collaboration, empathy, and self-regulation from an early age to foster positive peer relationships.